2015
DOI: 10.1016/j.bbamcr.2014.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib restores VASP activity and its interaction with Zyxin in BCR–ABL leukemic cells

Abstract: Vasodilator-stimulated phosphoprotein (VASP) and Zyxin are interacting proteins involved in cellular adhesion and motility. PKA phosphorylates VASP at serine 157, regulating VASP cellular functions. VASP interacts with ABL and is a substrate of the BCR-ABL oncoprotein. The presence of BCR-ABL protein drives oncogenesis in patients with chronic myeloid leukemia (CML) due to a constitutive activation of tyrosine kinase activity. However, the function of VASP and Zyxin in BCR-ABL pathway and the role of VASP in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Zyxin was also included in other models, demonstrating its importance for classifying ALL and AML, which is consistent with many studies (Crone et al, 2011;Bernusso et al, 2015;Tang et al, 2011;Hervy et al, 2010;Karimi and Farrokhnia, 2014;Joshi et al, 2016).…”
Section: Leukemia Datasupporting
confidence: 83%
“…Zyxin was also included in other models, demonstrating its importance for classifying ALL and AML, which is consistent with many studies (Crone et al, 2011;Bernusso et al, 2015;Tang et al, 2011;Hervy et al, 2010;Karimi and Farrokhnia, 2014;Joshi et al, 2016).…”
Section: Leukemia Datasupporting
confidence: 83%
“…In patients, an impaired LASP1-Y171 phosphorylation was seen under TKI therapy [11], but unfortunately, serine phosphorylation was not checked in that study. However, a recent publication showed imatinib-induced vasodilator-stimulated phosphoprotein (VASP) phosphorylation on S157 in K562 cells and in CML patients' bone marrow cells after imatinib treatment [51]. Completive data revealed a VASP-Y39 phosphorylation in BCR-ABL-positive leukemic cells [52].…”
Section: Discussionmentioning
confidence: 99%
“…One of such functions is to regulate cell migration through VASP phosphorylation [ 22 , 35 ]. VASP is an actin binding phosphoprotein implicated in the control of actin cytoskeleton elongation and cell migration [ 36 39 ], whose phosphorylation at Ser239 impairs actin assembly [ 22 , 36 , 37 ]. Consistently, we observed that in MCL cells, acadesine triggered VASP phosphorylation at Ser239, as well as blockade of actin polymerization and migration in MCL cells.…”
Section: Discussionmentioning
confidence: 99%